Performance ratio hardness characteristics polystyrene-metal composite materials - Klepikov, V.F.; Prokhorenko, E.M.; Lytvynenko, V.V.; Zakharchenko, A.A.; Hazhmuradov, M.A. (Вопросы атомной науки и техники, 2015)
The methods of measuring the hardness of layered polystyrene-metallic composite materials. It is proposed to use powder-like tungsten and powder-like steel as radiation-protective layer. A measurement of the hardness of composites of different composition, and given its dependence on the particle size and their form. The possibility of increasing the hardness of the composites reinforced with metallic additives. Radiation-protective characteristics were calculated for the studied species of composite materials. Influence of the quantitative composition of the metal components is studied on the change of the absorbed dose of gamma radiation. Відпрацьовані методики виміру твердості шаруватих полістиролметалевих композиційних матеріалів. Запропоновано використовувати як радіаційно-захисну добавку порошковий вольфрам і порошкову сталь. Проведено вимір значень твердості композитів різного складу і надана їх залежність від розмірів часток і їх форми. Показана можливість збільшення твердості композитів армуванням металевими добавками. Радіаційно-захисні характеристики розраховані для досліджених видів композиційних матеріалів. Вивчений вплив кількісного складу металевої компоненти на зміну поглиненої дози гама-випромінювання. Отработаны методики измерения твердости слоистых полистиролметаллических композиционных материалов. Предложено использовать в качестве радиационно-защитной добавки порошковый вольфрам и порошковую сталь. Проведено измерение значений твердости композитов различного состава и даны её зависимости от размеров частиц и их формы. Показана возможность увеличения твердости композитов армированием металлическими добавками. Радиационно-защитные характеристики рассчитаны для исследованных видов композиционных материалов. Изучено влияние количественного состава металлической компоненты на изменение поглощенной дозы гамма-излучения.